Let us consider the sums $$\displaystyle T_1(x)=\sum_{n\geq a\sqrt{x}}^{b \sqrt{x}} \left\{ \frac{x}{n} \right\} \\T_2(x)=\sum_{n\geq a\sqrt{x}}^{b \sqrt{x}} \left\{ \frac{x}{2n} \right\} $$ where $x$ is a positive integer, $0\leq a<b\leq 1$, $n$ runs over all integers in the interval $[a \sqrt{x}, b\sqrt{x}]$, and $\{ \}$ indicates the fractional part. Because of the equidistribution of such fractional parts, the plots of $T_1(x)$ and $T_2(x)$ versus $x$ show oscillations around the line $\frac{b-a}{2} \sqrt{x}$.

By experimental calculations, I noted that the average value of the difference between $T_1(x)$ (or $T_2(x)$) and $\frac{b-a}{2} \, \sqrt{x}$, calculated over all positive integers $x \leq N$, is $O(1)$. In particular, we have

$$\lim_{N \rightarrow \infty} \frac{1}{N} \sum_{x=1}^{N} \left( T_1(x)- \frac{b-a}{2} \sqrt{x} \right)= K_1(a,b)\\ \lim_{N \rightarrow \infty} \frac{1}{N} \sum_{x=1}^{N} \left( T_2(x)- \frac{b-a}{2} \sqrt{x} \right)= K_2(a,b)$$

where $K_1(a,b)$ and $K_2(a,b)$ are constant terms that depend on $a$ and $b$, indicating that the distributions of such differences are biased.

The problem can be simplified by considering the case where $b=1$ (once solved this case, the general case with $b<1$ can be solved by difference). In this case, the biases are determined only by $a$. For example, analyzing the distributions of differences over all integers $N$ up to $2500$, setting $a=0.5$ we have $K_1(0.5,1)\approx -0.370...$ and $K_2(0.5,1)\approx -0.169...$, with rather slow convergence rates. I wonder how these terms are generated and whether they could be exactly calculated. Again based on experimental results, it seems that $K_1$ and $K_2$ have a logarithmic relation with $a$, with values near to $\frac{1}{2} \log(a)$ and $\frac{1}{4} \log(a)$, respectively.

This question is somewhat linked to this other one, for which a nice answer was previously given.

EDIT (after Mathworker21's answer): A rough numerical computation until $N=10000$ for the case $a=0.5$, $b=1$ seems to confirm the above estimates obtained with $N$ up to $2500$. Here is the plot of the differences $T_1(x)- \frac{b-a}{2} \sqrt{x}$ versus $x$, followed by that of the average value of these differences calculated over the first $N$ integers. As show in this second plot, $K_1(0.5,1)$ seems to converge to $\approx -0.37$. The dotted black line in the first graph is the best fitting line, whose intercept is compatible with such value. Based on a visual assessment, large departures from this value (as suggested by the provided answer) for higher $N$ seem unlikely: enter image description here

Similar considerations can be made for $K_2(0.5,1)$, which seems to converge to $\approx -0.17$: enter image description here

  • 1
    $\begingroup$ You forgot to indicate what the problem is. $\endgroup$ – W-t-P Sep 7 '19 at 18:23
  • $\begingroup$ As stated in the OP, I would be happy to know whether these biases could be exactly calculated. In particular, I wonder whether it is possible to determine functions to express the biases given $a$. $\endgroup$ – Anatoly Sep 7 '19 at 20:03
  • $\begingroup$ @Anatoly $N=2500$ is way too small. The value of $K_1(0.5,1)$ is in fact much smaller (in absolute value) than $-0.370$. See my answer below. $\endgroup$ – mathworker21 Sep 8 '19 at 2:15
  • $\begingroup$ The values found for $N=2500$ are confirmed by the plots obtained with larger $N$. See my edit in the OP. $\endgroup$ – Anatoly Sep 8 '19 at 19:26
  • $\begingroup$ @mathworker21: You did really great work. Particularly, the alternative solution without trigs is very nice. Numerical computations probably agree with your result for $K_1$ (although with some small discrepancies, maybe arising from too small $N$ in the computations) . For $K_2$, discrepancies are a bit more evident: it seems that $K_2$ is $-1/4log(b/a)$ minus a small positive quantity (for example, numerical calculations give $K_2(0.25,1)approx -0.360$, and we have $-1/4 , log(4)=-0.346...$; adding $-(1-0.25^2)/12$ we arrive to $approx -0.42$, which is too negative). $\endgroup$ – Anatoly Sep 14 '19 at 10:56

Sigh, I hate fourier analysis. It turns people (especially me) into mindless, computing zombies.

The way to obtain $K_1(a,b)$ is literally just to interchange sums. I don't know why I didn't see this days ago. I don't have a fully rigorous proof, but I think it's just as rigorous as the fourier argument given in the other answer. This answer shows that $K_k(a,b) = \frac{-1}{2k}\log(\frac{b}{a})-\frac{k}{24}(b^2-a^2)$.

The intuitive reason the $\log$ appears is that $\frac{1}{2}$ is not the average value of $\{\frac{x}{m}\}$ for fixed $m$ as $x$ ranges. Instead, the average is $\frac{1}{m}\left[0+\frac{1}{m}+\dots+\frac{m-1}{m}\right] = \frac{m-1}{2m} = \frac{1}{2}-\frac{1}{2m}$. This "$\frac{-1}{2m}$" is the reason for the log. The reason for the $-\frac{k}{24}(b^2-a^2)$ is a bit harder to directly understand.

We assume $\frac{1}{a^2},\frac{1}{b^2}$ are integers that have the same residue modulo $k$. The result for any $a,b$ such that $\frac{1}{a^2}$ and $\frac{1}{b^2}$ are integers follows from an easy extension (to $k > 2$) of the reasoning given in the other answer.

$$\frac{1}{N}\sum_{x=1}^N \sum_{m=a\sqrt{x}}^{b\sqrt{x}} \left(\{\frac{x}{km}\}-\frac{1}{2}\right) = \frac{1}{N}\sum_{m=1}^{a\sqrt{N}}\sum_{x=m^2/b^2}^{m^2/a^2}\left(\{\frac{x}{km}\}-\frac{1}{2}\right)+\frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}}\sum_{x=m^2/b^2}^N \left(\{\frac{x}{km}\}-\frac{1}{2}\right)$$ Since we repeatedly cycle through the residues mod $km$, the first term is $$\frac{1}{N}\sum_{m=1}^{a\sqrt{N}} \frac{-1}{2}\left(\frac{\frac{m^2}{a^2}-\frac{m^2}{b^2}}{km}+O(1)\right) = \frac{-1}{4k}\left(1-\frac{a^2}{b^2}\right)+O\left(\frac{1}{\sqrt{N}}\right)$$ For each $m$, writing $N = q_m km+r_m$ for $0 \le r_m \le km-1$, the second term is $$\frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}}\sum_{x=m^2/b^2}^{q_m km} \left(\{\frac{x}{km}\}-\frac{1}{2}\right) + \frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \sum_{x=q_m km+1}^{q_m km+r_m} \left(\{\frac{x}{km}\}-\frac{1}{2}\right)$$ $$ = \frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \frac{-1}{2}\left(q_m-\frac{m}{b^2k}+O(1)\right) + \frac{1}{N}\sum_{a=\sqrt{N}}^{b\sqrt{N}} \left[\left(\frac{1}{km}-\frac{1}{2}\right)+\dots+\left(\frac{r_m}{km}-\frac{1}{2}\right)\right]$$ $$ = \frac{-1}{2k}\log(b/a)+\frac{1}{4k}(1-\frac{a^2}{b^2})+\frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \left(\frac{r_m(r_m+1)}{2km}-\frac{r_m}{2}\right)$$ The sum can be written as $$\frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \frac{mk}{2}(\frac{r_m}{km})^2-\frac{mk}{2}(\frac{r_m}{mk}),$$ and since $\frac{r_m}{mk} = \{\frac{N}{mk}\}$ should be equidistributed, and since $\int_0^1 x^2-x dx = \frac{-1}{6}$, we heuristically get $$\frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \frac{mk}{2}(-\frac{1}{6}) = \frac{-k}{24}(b^2-a^2).$$ Putting everything together gives the desired $$\lim_{N \to \infty} \frac{1}{N}\sum_{x=1}^N \sum_{m=a\sqrt{x}}^{b\sqrt{x}} \left(\{\frac{x}{km}\}-\frac{1}{2}\right) = \frac{-1}{2k}\log\left(\frac{b}{a}\right)-\frac{k}{24}\left(b^2-a^2\right).$$


We show $K_1(a,b) = -\frac{b^2-a^2}{24}-\frac{1}{2}\log(b/a)$. $K_2(a,b)$ can be found using the same methods used below.

The starting point is the identity $$\{\theta\}-\frac{1}{2} = \frac{-1}{\pi}\sum_{n=1}^\infty \frac{\sin(2\pi n\theta)}{n},$$ valid for $\theta \not \in \mathbb{Z}$ [Thanks to metamorphy for pointing out the invalidity for $\theta \in \mathbb{Z}$, and Anatoly for pointing it out again]. We show later that $$\lim_{N \to \infty} \frac{1}{N}\sum_{x=1}^N \sum_{\substack{m = a\sqrt{x} \\ m \mid x}}^{b\sqrt{x}} (\{\frac{x}{m}\}-\frac{1}{2}) = -\frac{1}{2}\log(b/a).$$

Using the fourier identity above, we obtain $$\frac{1}{N}\sum_{x=1}^N \sum_{\substack{m=a\sqrt{x} \\ m \not \mid x}}^{b\sqrt{x}} \left(\{\frac{x}{m}\}-\frac{1}{2}\right) = \frac{1}{N}\sum_{x=1}^N\sum_{m=a\sqrt{x}}^{b\sqrt{x}} \frac{-1}{\pi}\sum_{n=1}^\infty \frac{\sin(2\pi nx)}{n}.$$ For ease, we dropped the condition "$m \not \mid x$", which is allowed, since $\sin(2\pi n\frac{x}{m}) = 0$ if $m \mid x$. Since the outer two sums are finite, we may interchange to get $$\frac{-1}{\pi}\sum_{n=1}^\infty \frac{1}{n}\sum_{m=1}^{b\sqrt{N}}\frac{1}{N}\sum_{x=m^2/b^2}^{\min(m^2/a^2,N)} \sin(2\pi \frac{n}{m}x).$$ Suppose that $\frac{1}{a^2}$ and $\frac{1}{b^2}$ are integers, for ease. Using the identity $$\sin(\theta)+\dots+\sin(k\theta) = \frac{\cos(\frac{\theta}{2})-\cos((k+\frac{1}{2})\theta)}{2\sin(\frac{\theta}{2})},$$ we see that $$\sum_{x=m^2/b^2}^{m^2/a^2} \sin(2\pi\frac{n}{m}x) = \frac{1}{2\sin(\pi\frac{n}{m})}\left[\cos\left((\frac{m^2}{b^2}-1+\frac{1}{2})2\pi \frac{n}{m}\right)-\cos\left((\frac{m^2}{a^2}+\frac{1}{2})2\pi\frac{n}{m}\right)\right]$$ and $$\sum_{x=m^2/b^2}^N \sin(2\pi \frac{n}{m}x) = \frac{1}{2\sin(\pi\frac{n}{m})} \left[\cos\left((\frac{m^2}{b^2}-1+\frac{1}{2})2\pi\frac{n}{m}\right)-\cos\left((N+\frac{1}{2})2\pi\frac{n}{m}\right)\right].$$ Using again that $\frac{1}{a^2}$ and $\frac{1}{b^2}$ are integers, $$\cos\left((\frac{m^2}{b^2}-1+\frac{1}{2})2\pi \frac{n}{m}\right)-\cos\left((\frac{m^2}{a^2}+\frac{1}{2})2\pi\frac{n}{m}\right) = \cos\left(\frac{\pi n}{m}\right)-\cos\left(\frac{\pi n}{m}\right) = 0$$ and $$\cos\left((\frac{m^2}{b^2}-1+\frac{1}{2})2\pi\frac{n}{m}\right)-\cos\left((N+\frac{1}{2})2\pi\frac{n}{m}\right) = \cos\left(\frac{\pi n}{m}\right)-\cos\left(\frac{\pi n}{m}+2\pi\frac{N n}{m}\right).$$ Note that $$\cos(\frac{\pi n}{m}+2\pi\frac{N n}{m}) = \cos(\frac{\pi n}{m})\cos(2\pi\frac{N n}{m})-\sin(2\pi \frac{N n}{m})\sin(\frac{\pi n}{m}).$$ Putting everything together, $$\frac{1}{N}\sum_{x=1}^N \sum_{m=a\sqrt{x}}^{b\sqrt{x}} \left(\{\frac{x}{m}\}-\frac{1}{2}\right) = \frac{-1}{\pi}\sum_{n=1}^\infty \frac{1}{n}\frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \frac{\cos(\frac{\pi n}{m})[1-\cos(2\pi \frac{N n}{m})]+\sin(\frac{\pi n}{m})\sin(2\pi \frac{N n}{m})}{2\sin(\frac{\pi n}{m})}.$$ We handle the term $$\frac{-1}{\pi}\sum_{n=1}^\infty \frac{1}{n}\frac{1}{2N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \sin(2\pi \frac{N n}{m}) = \frac{1}{2N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \left(\{\frac{N}{m}\}-\frac{1}{2}\right) \to 0$$ as $N \to \infty$. Now, using $1-\cos(2\theta) = 2\sin^2(\theta)$, we are left with $$\frac{1}{N}\sum_{x=1}^N \sum_{m=a\sqrt{x}}^{b\sqrt{x}} \left(\{\frac{x}{m}\}-\frac{1}{2}\right) = \frac{-1}{\pi}\sum_{n=1}^\infty \frac{1}{n}\frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \frac{\sin^2(\pi \frac{N n}{m})\cos(\pi \frac{n}{m})}{\sin(\pi \frac{n}{m})}.$$ Let $$c_{n,N} = \frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \frac{\sin^2(\pi\frac{Nn}{m})\cos(\frac{\pi n}{m})}{\sin(\frac{\pi n}{m})}.$$ We prove afterwards that, for any fixed $n$, $$\lim_{N \to \infty} c_{n,N} = \frac{1}{n}\frac{b^2-a^2}{4\pi}.$$ Using $$\lim_{N \to \infty} \frac{-1}{\pi}\sum_{n=1}^\infty c_{n,N} = \frac{-1}{\pi}\sum_{n=1}^\infty \lim_{N \to \infty} c_{n,N},$$ which we justify later, we finally obtain $$\frac{1}{N}\sum_{x=1}^N \sum_{\substack{m=a\sqrt{x} \\ m \not \mid x}}^{b\sqrt{x}} \left(\{\frac{x}{m}\}-\frac{1}{2}\right) = \frac{-1}{\pi}\sum_{n=1}^\infty \frac{1}{n^2}\frac{b^2-a^2}{4\pi} = -\frac{b^2-a^2}{24}.$$

We first show $$\lim_{N \to \infty} \frac{1}{N}\sum_{x=1}^N \sum_{\substack{m = a\sqrt{x} \\ m \mid x}}^{b\sqrt{x}} (\{\frac{x}{m}\}-\frac{1}{2}) = -\frac{1}{2}\log(b/a).$$ Of course, $\{\frac{x}{m}\} = 0$ if $m \mid x$. Interchanging summations, $$\frac{1}{N}\sum_{x=1}^N \sum_{\substack{m=a\sqrt{x} \\ m \mid x}}^{b\sqrt{x}} 1 = \frac{1}{N}\sum_{m=1}^{a\sqrt{N}} \sum_{\substack{m^2/b^2 \le x \le m^2/a^2 \\ m \mid x}} 1 + \frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \sum_{\substack{m^2/b^2 \le x \le N \\ m \mid x}} 1.$$ $$ = \frac{1}{N}\sum_{m=1}^{a\sqrt{N}} [\frac{m}{a^2}-\frac{m}{b^2}+O(1)]+\frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} [\lfloor \frac{N}{m}\rfloor -\frac{m}{b^2}+O(1)] = \log(b/a)+O(\frac{1}{\sqrt{N}}).$$

We now prove that, for any fixed $n \ge 1$, $$\lim_{N \to \infty} \frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \frac{\sin^2(\pi\frac{N n}{m})\cos(\frac{\pi n}{m})}{\sin(\frac{\pi n}{m})} = \frac{1}{n}\frac{b^2-a^2}{4\pi}.$$ As $\cos(\frac{\pi n}{m}) = 1+O(\frac{1}{m^2})$, and $\sin^2(\pi \frac{N n}{m}) \le 1$ and $\sin(\frac{\pi n}{m}) \gtrsim \frac{1}{m}$, we may replace $\cos(\frac{\pi n}{m})$ by $1$. Similarly, since $\sin(\frac{\pi n}{m}) \ge \frac{\pi n}{m}-c\frac{\pi^3}{n^3}{m^3}$, we may replace $\sin(\frac{\pi n}{m})$ by $\frac{\pi n}{m}$. We are left with $$\frac{1}{\pi n}\frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} m\sin^2\left(\pi \frac{N n}{m}\right).$$ Using again that $\sin^2(\theta) = \frac{1-\cos(2\theta)}{2}$, it suffices to show $$\frac{1}{N}\sum_{n=a\sqrt{N}}^{b\sqrt{N}} m\cos(2\pi\frac{N n}{m}) \to 0.$$ It clearly then suffices to show $$\frac{1}{N}\sum_{m=1}^{c\sqrt{N}} m\cos(2\pi \frac{N n}{m}) \to 0$$ for any fixed $c \in (0,1)$. By summation by parts, $$\frac{1}{N}\sum_{m=1}^{c\sqrt{N}} m\cos(2\pi \frac{N n}{m}) = \frac{1}{N}(c\sqrt{N})\sum_{m=1}^{c\sqrt{N}} \cos(2\pi \frac{N n}{m}) - \frac{1}{N}\int_1^{c\sqrt{N}} \left[\sum_{m \le t} \cos(2\pi \frac{N n}{m})\right]dt,$$ so it suffices to show some nontrivial amount of equidistribution of $\{\frac{N n}{m}\}$ for $m \le c\sqrt{N}$, which shouldn't be too bad.

Now we handle $K_2(a,b)$. We show that $K_2(a,b) = -\frac{b^2-a^2}{12}-\frac{1}{4}\log(b/a)$ if $\frac{1}{a^2},\frac{1}{b^2}$ are integers of the same parity. This can be extended to the case of $\frac{1}{a^2},\frac{1}{b^2}$ any integers. Take, for example, $a = \frac{1}{2}, b = 1$. For any $k \ge 1$, we have $$K_2(\frac{1}{2},1) = K_2(\frac{1}{3},1)-K_2(\frac{1}{4},\frac{1}{2})+K_2(\frac{1}{5},\frac{1}{3})-K_2(\frac{1}{6},\frac{1}{4})+\dots+K_2(\frac{1}{2k+1},\frac{1}{2k-1})-K_2(\frac{1}{2k+1},\frac{1}{2k}).$$ Since $K_2(\frac{1}{2k+1},\frac{1}{2k}) \le K_2(\frac{1}{2k+1},\frac{1}{2k-1})$ can be made arbitrarily small, we get, after a brief computation, $K_2(\frac{1}{2},1) = -\frac{1-.5^2}{12}-\frac{1}{4}\log(1/.5)$.

Similar to before, $$\frac{1}{N}\sum_{x=1}^N \sum_{\substack{m \ge a\sqrt{x} \\ 2m \mid x}}^{b\sqrt{x}} 1 = \frac{1}{N}\sum_{m=1}^{a\sqrt{N}}\sum_{\substack{m^2/b^2 \le x \le m^2/a^2 \\ 2m \mid x}} 1 + \frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \sum_{\substack{m^2/b^2 \le x \le N \\ 2m \mid x}} 1$$ $$= \frac{1}{N}\sum_{m=1}^{a\sqrt{N}} \frac{m}{2}(\frac{1}{a^2}-\frac{1}{b^2})+\frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \frac{N-\frac{m^2}{b^2}}{2m} = \frac{1}{2}\log(b/a)+O(\frac{1}{N}).$$ Therefore, $$\frac{1}{N}\sum_{x=1}^N \sum_{\substack{m \ge a\sqrt{x} \\ 2m \mid x}} \left(\{\frac{x}{2m}\}-\frac{1}{2}\right)$$ contributes a $\frac{-1}{4}\log(b/a)$. As before, we do $$\frac{1}{N}\sum_{x=1}^N \sum_{\substack{m \ge a\sqrt{x} \\ 2m \not \mid x}}^{b\sqrt{x}} \frac{-1}{\pi}\sum_{n=1}^\infty \frac{\sin(2\pi n \frac{x}{2m})}{n}.$$ Dropping the condition "$2m \not \mid x$" (which is permissible), interchanging sums, and using the sum-of-sines formula again, and noting that $$\cos\left((\frac{m^2}{b^2}-\frac{1}{2})\pi \frac{n}{m}\right)-\cos\left((\frac{m^2}{a^2}+\frac{1}{2})\pi\frac{n}{m}\right) = 0$$ since $\frac{1}{b^2},\frac{1}{a^2}$ are even, we obtain $$\frac{-1}{\pi}\sum_{n=1}^\infty \frac{1}{n} \frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \frac{\cos(\frac{\pi n}{2m})-\cos(N \pi \frac{n}{m})\cos(\frac{\pi n}{2m})+\sin(N \pi \frac{n}{m})\sin(\frac{\pi n}{2m})}{2\sin(\frac{\pi n}{2m})}.$$ As before, $$\frac{1}{2}\frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \frac{-1}{\pi}\sum_{n=1}^\infty \frac{\sin(N\pi \frac{n}{m})}{n} = \frac{1}{2}\frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \left(\{\frac{N}{2m}\}-\frac{1}{2}\right) \to 0.$$ As before, we should have $$\frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \frac{\cos(N\pi \frac{n}{m})\cos(\frac{\pi n}{2m})}{\sin(\frac{\pi n}{2m})} \to 0$$ as $N \to \infty$ for any fixed $n \ge 1$. And, for any fixed $n \ge 1$, as $N \to \infty$, we have $$\frac{1}{N}\sum_{m=a\sqrt{N}}^{b\sqrt{N}} \frac{\cos(\frac{\pi n}{2m})}{2\sin(\frac{\pi n}{2m})} \to \frac{1}{n}\frac{b^2-a^2}{2\pi},$$ so $$\frac{1}{N}\sum_{x=1}^N\sum_{\substack{m = a\sqrt{x} \\ 2m \not \mid x}}^{b\sqrt{x}} \left(\{\frac{x}{2m}\}-\frac{1}{2}\right) = -\frac{b^2-a^2}{12}.$$

  • $\begingroup$ Comments are not for extended discussion; this conversation has been moved to chat. $\endgroup$ – Aloizio Macedo Sep 14 '19 at 6:40

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.